Global demand for rice genetic resources - Jamora, Nelissa; Ramaiah, Venuprasad (Springer, 2022)
The International Rice Research Institute (IRRI) holds in trust the world's largest collection of rice diversity, with more than 130,000 accessions of cultivated rice and wild species. Between 2012 and 2018, a total of 2174 requests for rice germplasm were received from more than 1000 unique requestors. We documented and analyzed how genebank users made use of germplasm from IRRI. As we address food and nutrition security challenges in a changing context, we are motivated by the need to enhance the conservation, management, and use of rice genetic resources.